Ideal skills for European food scientists and technologists: identifying the most desired knowledge, skills and competencies - Flynn, Katherine (2017)
Training food scientists and technologists (FSTs) to have appropriate skills begins with identification of those skills most desired by employers. Between March 2010 and August 2011, 16 workshops in 16 countries had 315 local FST employers contribute ideas of skills desired in their FSTs. Attendees provided as many skills as possible and these descriptive data were quantifed and then analysed with multiple contingency tables and chi squared testing. Of the 3348 skill ideas provided, the most desired skill overall was Communicating, which was identified 13% of the time. Separate analysis of the 792 food sector skills indicated Product Development, at 28%, as the most desired. Geographical region, employment area and FST level of responsibility all significantly influenced the top 3 choices of overall skills and of food sector skills, indicating that most desired skills in the food industry are not uniform. These results should contribute to the improvement of FST training and thus benefit the European food industry. Industrial relevance: The data presented here suggest that improvements in FST training, particularly the acquisition of 'soft skills', will improve Europe's food workforce as these are the skills employers most desire. These data further suggest that geographical region significantly influences those skills most desired by industrial employers. Differences in desired skills at different levels of FST responsibility further suggest that continual FST training i.e., continual professional development, will contribute to improved FST performance. Overall, this study presents data which can improve FST performance and thus contribute to increased innovation and competitiveness of the food and drink industry.